Retracted: A retrospective study on middle ear risk indices in analysing the postoperative outcome following tympanoplasty - Vignadutt, P.; Shaik, Ali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
The article "A retrospective study on middle ear risk indices in analysing the postoperative outcome following tympanoplasty" is retracted by the Editor-in-Chief, on the request of corresponding author and co-author, due to violation of the policies and practices of International Journal of Otorhinolaryngology and Head and Neck Surgery. The authors communicated the above article without knowledge of the principal investigator, Dr. Roopak and co researchers involved in the study. The principal investigator informed to the Editor-in-Chief regarding plagiarism of the data from his unpublished research paper.